Memahami Konsep al-Ibtila’ Dalam Islam Menerusi Konsepsi, Klasifikasi, Bentuk, Tujuan dan Manfaat: Understanding The Concept of al-Ibtila' In Islam Through The Concept, Classification, Form, Purpose and Benefits - Syed Abdul Rahman, Syed Mohammad Hilmi; Mohammed Dawam, Rohaida; Mohd Azhar, Muhammad Hazim (Online Journal of Research in Islamic Studies, 2020)
Believing in Allah’s Qada’ and Qadar is one of the pillars of faith for Muslim. One of the important elements in this particular pillar of faith is the concept of al-Ibtila’. In the context of Malay Muslims, the word al-Ibtila’ is rarely used, or at least not as frequently used as its synonym, Bala’. Al-Ibtila’ is commonly understood in the form of hardship and difficulties in life, but in fact it also includes worldly pleasure and luxury. It is therefore very important for Muslims to understand the concept of Ibtila’ in Islam. This paper aims to explore the concept of Ibtila’ according to Islam by covering some important elements which include its basic concepts, classification, form, purpose, and benefits. By knowing and understanding the concept of Ibtila’ in Islam, the soul can be taught to be patient and steadfast when facing trials and adversity.